2021
DOI: 10.1590/0037-8682-602-2020
|View full text |Cite
|
Sign up to set email alerts
|

Brazilian Protocol for Sexually Transmitted infections, 2020: pelvic inflammatory disease

Abstract: Pelvic Inflammatory Disease is a topic included in the Clinical Protocol and Therapeutic Guidelines for Comprehensive Care for People with Sexually Transmitted Infections, published by the Brazilian Ministry of Health in 2020. Pelvic inflammatory disease is an upper female genital tract acute infection due to canalicular spread of endogenous cervicovaginal microorganisms and especially the sexually transmitted microorganisms. Standing out among the etiological agents involved are Chlamydia trachomatis and Neis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…PID is responsible for 30% of cases of infertility due to tubal factors and 50% of cases of ectopic pregnancies due to tubal occlusion, in addition to being associated with premature birth and spontaneous abortion [13][14][15][16][17][18][19][20][21]. In Brazil, the absence of a monitoring program contributes to the unawareness of this silent epidemic and its recurrent damages, however, the annual number of hospitalizations of women with PID is over 45,000 [22]. The studies have reported prevalence of 4-20.5% in both asymptomatic women [23][24][25][26][27][28][29][30][31] and those seeking gynecological treatment [32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…PID is responsible for 30% of cases of infertility due to tubal factors and 50% of cases of ectopic pregnancies due to tubal occlusion, in addition to being associated with premature birth and spontaneous abortion [13][14][15][16][17][18][19][20][21]. In Brazil, the absence of a monitoring program contributes to the unawareness of this silent epidemic and its recurrent damages, however, the annual number of hospitalizations of women with PID is over 45,000 [22]. The studies have reported prevalence of 4-20.5% in both asymptomatic women [23][24][25][26][27][28][29][30][31] and those seeking gynecological treatment [32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the use of gentamicin in a single daily dose, as shown in Figure 5 "Pelvic inflammatory disease treatment" in our publication 1 , we emphasize that this is the recommended dosage for in-hospital treatment, as it is at least as effective, or perhaps even more effective, than a fractionated dose. It is of lower cost, requires less intervention, and has lower nephrotoxicity than multiple daily dose regimens.…”
mentioning
confidence: 95%
“…We would like to thank Dr. Savaris for his relevant comments on our article (https://doi.org/10.1590/0037-8682-0419-2021) 1 . His letter emphasizes three basic points: 1) diagnostic criteria for pelvic inflammatory disease (PID), 2) benefits in the use of gentamicin as a single dose rather than in two or three daily doses, and 3) suitability of antibiotic usage prior to intrauterine device (IUD) removal or even the need for its removal for the treatment of PID.…”
mentioning
confidence: 99%
“…It was with great interest that I read the article published by Menezes et al on pelvic inflammatory disease, in a recent publication of the JBSTM 1 , which was a review of the Clinical Protocol and Therapeutic Guidelines for Comprehensive Care for People with Sexually Transmitted Infections, published by the Health Surveillance Secretariat of the Brazilian Ministry of Health. Although it has been reported that the protocol was developed through the selection and analysis of available evidence, followed by discussions with specialists, I would like to share some comments about the "new" evidence provided in the 2020 Brazilian Guidelines.…”
mentioning
confidence: 99%
“…For these reasons, the current diagnosis of PID, proposed by the Centers of Disease Control and Prevention (CDC) 3 , has replaced the outdated criteria proposed by Hager et al in 1983 4 and last seen in the CDC 1998 Guidelines for Treatment of STDs 5 . Unfortunately, recent publications from the Brazilian scientific society and the Brazilian government still use the outdated 3 major + 1 minor criteria 1 ),( 6 , despite citing an article with the new CDC criteria 2 . These "new" CDC criteria for PID can be traced back to 2002 7 .…”
mentioning
confidence: 99%